Conformational H-bonding modulation of the iron active site cysteine ligand of superoxide reductase: absorption and resonance Raman studies. Issue 8 (2nd February 2021) - Desbois, Alain; Valton, Julien; Moreau, Yohann; Torelli, Stéphane; Nivière, Vincent
Abstract : Superoxide reductase Asn117 residue, by making hydrogen bonds with neighboring residues, enables fine-tuning of the Fe–S(Cys116) bond strength. Abstract : Superoxide reductases (SORs) are mononuclear non-heme iron enzymes involved in superoxide radical detoxification in some microorganisms. Their atypical active site is made of an iron atom pentacoordinated by four equatorial nitrogen atoms from histidine residues and one axial sulfur atom from a cysteinate residue, which plays a central role in catalysis. In most SORs, the residue immediately following the cysteinate ligand is an asparagine, which belongs to the second coordination sphere and is expected to have a critical influence on the properties of the active site. In this work, in order to investigate the role of this asparagine residue in the Desulfoarculus baarsii enzyme (Asn117), we carried out, in comparison with the wild-type enzyme, absorption and resonance Raman (RR) studies on a SOR mutant in which Asn117 was changed into an alanine. RR analysis was developed in order to assign the different bands using excitation in the (Cys116)–S − → Fe 3+ charge transfer band. By investigating the correlation between the (Cys116)–S − → Fe 3+ charge transfer band maximum with the frequency of each RR band in different SOR forms, we assessed the contribution of the ν (Fe–S) vibration among the different RR bands. The data showed that Asn117, by making hydrogen bond interactions with Lys74 and Tyr76, allows a rigidification of the backbone of the Cys116 ligand, as well as that of the neighboring residues Ile118 and His119. Such a structural role of Asn117 has a deep impact on the S–Fe bond. It results in a tight control of the H-bond distance between the Ile118 and His119 NH peptidic moiety with the cysteine sulfur ligand, which in turn enables fine-tuning of the S–Fe bond strength, an essential property for the SOR active site. This study illustrates the intricate roles of second coordination sphere residues to adjust the ligand to metal bond properties in the active site of metalloenzymes.